Analysis of the physical-chemical, microbiological and organoleptic profiles of craft and industrial Pilsen type beers marketed in the Metropolitan Region of Belém-PA (Research, Society and Development, 2023)
Produced in an industrial or artisanal way, beers are usually composed of water, hops and malt, and may have other ingredients in their recipe such as wheat, rice or corn. In Brazil, beers are mostly industrially produced, but craft beers have been gaining prominence in the market due to their different colors, production methods, alcoholic strengths and flavors. The objective of this research was to analyze the physical-chemical, microbiological and organoleptic characteristics of three beers, one industrial and two artisanal Pilsen type, sold in the Metropolitan Region of Belém-PA. The results of the physical-chemical analyzes were satisfactory for all analyses. The organoleptic analyzes showed an acceptance pattern as recommended by the literature or legislation, as well as the microbiological analyzes that showed the absence of salmonella, bacteria, molds and yeasts. Thus, the importance of physical-chemical, microbiological and organoleptic quality controls is observed, in view of the lack of data for craft beers in Brazil.